Food Producing Facades Key to a Sustainable Future - Christopher Paul Leınınger (DEPARCH Journal of Design Planning and Aesthetics Research)
The built environment uses substantial and increasing amounts of energy, contributing to Urban Heat Island effect, while population growth and urban development have outpaced food production globally. There is a growing trend to introduce green infrastructure into the built environment via green roofs, green facades, and urban agriculture. Research is limited, however, into the use of food producing plants being grown on a living façade to improve total building performance. The purpose of this research study was to test the assertion that food producing plants can be grown successfully in a vertical greenery system or green wall integrated into an existing commercial building façade. Specifically, this dissertation investigates the role of integrating food producing plants into a living facade to positively impact four outcomes: food production, thermal performance, air quality and rainwater management in a temperate climate. This was a six-year long longitudinal research study. The findings from this study conclusively demonstrate that a maximum average production of 2.64 kilograms of produce per square meter of façade panel can be generated annually (0.54 lbs./ft2). The façade temperatures were reduced between 5.56oC-20.53oC (10oF-36.95oF) with approximately 20% reduction in cooling energy, reducing urban heat island. Airborne small particulates (PM2.5 )were reduced a maximum of 5.6% for the living facade compared to the control. An average of 14.26 liters of rooftop rainwater per square meter of facade per day (0.35 gal/ft2/day) was used for irrigation. In addition, observational studies revealed enhanced access to nature for building occupants, wildlife habitat and biodiversity.